Planning pathways in the transfer of Directly Observed Treatment of Tuberculosis (Revista Latino-Americana de Enfermagem, 2019)
Objective: to investigate the planning pathways in the transfer of Directly Observed Treatment of tuberculosis. Method: a qualitative study conducted using interviews and a semi-structured guide, administered to five subjects who were among the coordinators and managers of the tuberculosis control programs, and the secretary of health of a municipality in the south of Brazil. Situational Strategic Planning and Discourse Analysis of the French matrix were the theoretical and analytical references used, respectively. Results: three reflexive axes were identified: weaknesses in the process of planning the Directly Observed Treatment transfer, antagonism between planning and daily requirements and formulation of planning and execution. Lack of systematization regarding the planning and execution for transfer the Directly Observed Treatment policy, demonstrates the fragility and incipience of this activity, and the possibility of its non-existence. Conclusion: the urgent need for managers and coordinators to better appropriate the theoretical framework for changing public policies, and the related planning mechanisms, includes a proposal for reorganization and qualification of the diffusion process, both practical-operative and political-organization.